2003
DOI: 10.3171/spi.2003.99.2.0221
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biomechanical effects of reconstruction on adjacent motion segment: comparison of aligned/kyphotic posterolateral fusion with aligned posterior lumbar interbody fusion/posterolateral fusion

Abstract: Object. Posterior lumbar interbody fusion (PLIF) was developed to overcome the limitations of posterolateral fusion in correcting spinal deformity and maintaining lumbar lordosis. In this study the authors compare the biomechanical effects of three different posterior reconstructions on the adjacent motion segment. Methods. Ten calf spinal (L2—S1) specimens underwent nondestructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
1
23
1
1
Order By: Relevance
“…The calf is the species mainly used in vitro. Tests with pedicle screw systems are counted among these experiments [3,4,6,9,11,17,18]. According to the results of the present study, these experiments reveal the right trends but should not be interpreted quantitatively.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The calf is the species mainly used in vitro. Tests with pedicle screw systems are counted among these experiments [3,4,6,9,11,17,18]. According to the results of the present study, these experiments reveal the right trends but should not be interpreted quantitatively.…”
Section: Discussionmentioning
confidence: 72%
“…Similar to the calf, the pig is also often used in vitro. Both calf and pig are models used to measure IDP [1,8,[12][13][14]18]. These measurements reveal the implant's general effects on intradiscal pressure expected in healthy human intervertebral discs but may differ from the human in magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…1,18,20,21 The flexion and extension moments ranged from 0 to 6 N-m, which include the ranges of moments used in previous biomechanical studies using lumbar reconstruction models. 1,9,10,18,21 As pilot studies have previously demonstrated that load-displacement and load-strain or pressure data after the second load-unload cycle were almost identical to the second, the loading procedure involved the application of a three load-unload cycle. The third loading cycle was used for data analysis of all biomechanical parameters.…”
Section: Specimens and Experimental Setupmentioning
confidence: 99%
“…A displacement gauge (Model 25C-20, MTS Systems, Inc. Minneapolis, MN) spanning the operative segment was utilized to quantify segmental displacement 18,21 (if two-segment fusion was simulated, the gauge was placed over the whole fusion length of L5 to S1 the lateral side of the L4-5 intervertebral disc into the center of the nucleus pulposus. 6,21 The insertion point and depth of the needle was controlled using both anterior-posterior and lateral radiographs. Uniaxial surface-strain gauges (KFG-02-120-C1-11L3M2R; Kyowa Dengyo Co., Tokyo, Japan) were sagittally mounted on the bilateral L4 lamina just craniad to the L4-L5 facet joint by using cyanoacrylate.…”
Section: Specimens and Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation